2009
DOI: 10.1007/s00125-009-1626-y
|View full text |Cite
|
Sign up to set email alerts
|

Gut barrier disruption by an enteric bacterial pathogen accelerates insulitis in NOD mice

Abstract: Aims/hypothesis Increased exposure to enteric microbes as a result of intestinal barrier disruption is thought to contribute to the development of several intestinal inflammatory diseases; however, it less clear whether such exposure modulates the development of extra-intestinal inflammatory and autoimmune diseases. The goal of this study was to examine the potential role of pathogenic enteric microbes and intestinal barrier dysfunction in the pathogenesis of type 1 diabetes. Methods Using NOD mice, we assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
101
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 44 publications
4
101
0
1
Order By: Relevance
“…46,47). Breach of the gastrointestinal barrier with subsequent leakage of potentially immunogenic dietary components has been proposed to promote T1D in NOD mice (48) and is a well-established trigger of celiac disease, an anti-gliadin-directed autoimmune disorder that frequently accompanies T1D in humans (49,50). Moreover, we previously demonstrated that gut irritation in NOD mice alters the priming of diabetogenic islet-derived self-antigens in the PLNs (31).…”
Section: Discussionmentioning
confidence: 97%
“…46,47). Breach of the gastrointestinal barrier with subsequent leakage of potentially immunogenic dietary components has been proposed to promote T1D in NOD mice (48) and is a well-established trigger of celiac disease, an anti-gliadin-directed autoimmune disorder that frequently accompanies T1D in humans (49,50). Moreover, we previously demonstrated that gut irritation in NOD mice alters the priming of diabetogenic islet-derived self-antigens in the PLNs (31).…”
Section: Discussionmentioning
confidence: 97%
“…In recent T1D and CD investigations, intestinal microbiota have received attention as possible modulators of disease development. [27][28][29][30] However, one could ask whether the detection of serum antibodies against antigens of a particular commensal bacteria reflects its presence and involvement in immune reactions at the intestinal level. Although it is possible that we detected antibodies induced by antigens that originated from other microorganisms, we are still confident that a portion of the detected antibodies was directed against B. adolescentis itself or other Bifidobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] In experimentally induced diabetes in rats or mice, changes in intestinal permeability are also detected before the onset of diabetes; increased intestinal permeability in these cases has been shown to be dependent on increased zonulin expression, which regulates tight junctions in the intestinal mucosa. [25][26][27] Additionally, mucosal biopsy, fecal microbiota and serological studies have indicated that the composition of intestinal microbiota may influence the immune mechanisms that participate in the development of CD 28,29 and T1D. 27,29,30 Consistent with these studies, recent investigations have stressed the importance of Bifidobacteria species and strains in the modulation of immune reactivity at the intestinal mucosa level.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Virus infections are hypothesised to contribute to diabetes development by three distinct but not mutually exclusive general mechanisms: pancreatic infection, T cell molecular mimicry and bystander activation. Increased intestinal inflammation and permeability have also been implicated in diabetes development [4], and certain bacterial infections and intestinal microbiota may modulate diabetes in these ways [10,11]. Here we briefly discuss the potential roles of pancreatic infection and molecular mimicry, which have been extensively reviewed previously [12,13].…”
Section: Introductionmentioning
confidence: 99%